A Decade of Nutrition and Health Disparities Research at NIH, 2010–2019. (7th June 2021) - Brown, Alison; Shi, Scarlet; Adas, Samantha; Boyington, Josephine; Paul, Cotton; Jirles, Bill; Rajapakse, Nishadi; Reedy, Jill; Regan, Karen; Weatherspoon, Darien; Xi, Dan; Zappalà, Giovanna; et al.
Abstract: Objectives: Nutrition health disparities include the differences in incidence, prevalence, morbidity, and mortality of diet-related diseases and conditions that disproportionally affect disadvantaged groups (e.g., race, ethnicity, socioeconomic status, disability, rural, immigration status). These disparities arise from the complex interaction of individual, interpersonal, community, and societal factors within the biological, behavioral, and environmental domains. The purpose of this study is to describe the scope of nutrition health disparities research supported by the National Institutes of Health (NIH) over the past decade to identify research gaps and opportunities relevant to NIH's mission. Methods: Data were extracted from an internal reporting system from 2010 to 2019 using the Research, Condition, and Disease Categorization (RCDC) spending categories for "Nutrition" and "Health Disparities." Results: Over the past decade, the number of NIH supported nutrition and health disparities research studies have generally increased, with 860 grants funded in 2010 and 937 grants in 2019, while total nutrition and health disparities funding remained relatively stable. The top 5 Institutes/Centers that funded nutrition and health disparities research included the National Institute of Diabetes and Digestive and Kidney Diseases, National Heart Lung and Blood Institute, Eunice Kennedy Shriver National Institute of Child Health and Human Development, National Cancer Institute, and National Institute on Minority Health and Health Disparities. Conclusions: Consistent with the mission of the top funding ICs, the top research areas were obesity, diabetes, digestive diseases, cancer, heart disease, clinical research, prevention, and behavioral and social sciences. Cross-cutting topics relevant to all NIH ICs included special populations areas such as pediatric and minority health followed by aging and women's health. Consistent with the Strategic Plan for NIH Nutrition Research, it is critical to advance health equity through the application of precision nutrition approaches that acknowledge the influence of biologic, behavioral, psychosocial, environmental, and social factors on nutrition health disparities, and to develop effective targeted interventions to address these disparities. Funding Sources: None.